2020
DOI: 10.1371/journal.pone.0235990
|View full text |Cite|
|
Sign up to set email alerts
|

Drug targeting CYP2E1 for the treatment of early-stage alcoholic steatohepatitis

Abstract: Background and aims Alcoholic steatohepatitis (ASH)-the inflammation of fatty liver-is caused by chronic alcohol consumption and represents one of the leading chronic liver diseases in Western Countries. ASH can lead to organ dysfunction or progress to hepatocellular carcinoma (HCC). Long-term alcohol abstinence reduces this probability and is the prerequisite for liver transplantation-the only effective therapy option at present. Elevated enzymatic activity of cytochrome P450 2E1 (CYP2E1) is known to be criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 62 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…A model HCC cell line (HepG2 cells) and a model colorectal cancer cell line (DLD-1 cells) were used because the development and progression of both diseases are associated with CYP2E1 [ 16 , 23 ]. Because we have already shown that I-ol was effective in treating ASH [ 24 ] and NASH (unpublished data), I-ol was tested for efficacy against hepatocarcinogenesis. A further rationale for this proof-of-concept study was the potential for evaluating the possible extension of I-ol for treating the lethal end stage of FLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A model HCC cell line (HepG2 cells) and a model colorectal cancer cell line (DLD-1 cells) were used because the development and progression of both diseases are associated with CYP2E1 [ 16 , 23 ]. Because we have already shown that I-ol was effective in treating ASH [ 24 ] and NASH (unpublished data), I-ol was tested for efficacy against hepatocarcinogenesis. A further rationale for this proof-of-concept study was the potential for evaluating the possible extension of I-ol for treating the lethal end stage of FLD.…”
Section: Discussionmentioning
confidence: 99%
“…One of our studies showed that ROS production in cultured HepG2 cells was low and was accompanied by low CYP2E1 enzymatic activity. Treatment with 40 μ M I-ol led to a reduction of both parameters, but these differences were not statistically significant [ 24 ]. This observation correlates with the finding that both parameters reach their maximum in cirrhotic livers but decrease to a minimum during the transition to HCC development [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed, in an animal model, that I‐ol and I‐an, two new CYP2E1 enzyme inhibitors, are excellent drug candidates for the treatment of ASH (S7 Fig) (Diesinger et al, 2020). In the present study, we investigated whether they are as suitable for NASH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…for both drug candidates. These observations could be correlated with the binding strength of the inhibitors to CYP2E1, which indicated that I-ol exhibited the highest affinity, followed by I-an (Diesinger et al, 2020). Overall, however, the acute toxic effect of both substances was so low that no classification system, according to the usual criteria, could be used (Walum, 1998).…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation